FUNGSI FILSAFAT ISLAM DAN MANFAAT MEMPELAJARI FILSAFAT ISLAM - Suhari Suhari (ADISAM PUBLISHER, 2023)
The philosophy of Islamic education is essentially a concept of thinking about education that is sourced or based on the teachings of the Islamic religion. The philosophy of Islamic education is a discussion of the nature of Muslims' abilities to be nurtured, developed and guided, so that they become human beings whose entire personality is imbued with Islamic teachings. This journal tries to discuss the function of Islamic philosophy and the benefits of studying Islamic philosophy. The approach used in studying this topic is a literature study in which the literature taken is adjusted to the subject matter and analyzed in depth so that conclusions, findings can be drawn and can be studied as source of information in the future.